2011
DOI: 10.2174/1874259901105010001
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Upregulation in the Liver after Bile Duct Ligation in Rats

Abstract: Abstract:Background: Transforming growth factor beta 1 (TGF-1) has been implicated in the stimulation of extracellular matrix synthesis in acute and chronic liver disease. Endoglin (CD-105) is a membrane glycoprotein that binds TGF-1 with high affinity. Endoglin is overexpressed in several model of fibrosis. The goal of the present study was to evaluate the effect of bile duct ligation (BDL) on endoglin expression and the effect of endoglin overexpression on liver fibrosis in rats.Methods: Rat livers were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A recent study by another group reported a similar increase in endoglin expression in the liver following bile duct ligation in rats, but transfection of human endoglin did not alter liver fibrosis (Pérez‐Barriocanal et al 2011). These findings suggest that generalized overexpression of endoglin in the liver may not alter the fibrotic process in the liver.…”
mentioning
confidence: 86%
“…A recent study by another group reported a similar increase in endoglin expression in the liver following bile duct ligation in rats, but transfection of human endoglin did not alter liver fibrosis (Pérez‐Barriocanal et al 2011). These findings suggest that generalized overexpression of endoglin in the liver may not alter the fibrotic process in the liver.…”
mentioning
confidence: 86%
“…Histological features of liver specimens were analyzed with the METAVIR group scoring system [13]. The core biopsies were more than 10 mm in length and contained at least 8 portal tracts.…”
Section: Liver Biopsymentioning
confidence: 99%